2004
DOI: 10.1111/j.1464-410x.2004.04600.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sampling more cores on the predictive accuracy of pathological grade and tumour distribution in the prostate biopsy

Abstract: The technique for taking prostatic biopsies has received a major evaluation from many departments around the world in terms of the number of cores, site of biopsy, complications, need for local anaesthesia or sedation, etc., and the authors from Charlottesville review their technique. They present data confirming the impression that increasing the number of cores increases diagnostic sensitivity. Authors from Chapel Hill have performed a pilot study into the concept that cyclooxygenase (COX)‐2 inhibitors inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…It has been demonstrated that the probability of detecting prostate carcinoma and the accuracy of pathologic grading both increase with increasing number of biopsy cores obtained. 12,13 The number of cores found to be positive for malignancy also varies according to the number of cores obtained, as does the probability of detecting an elevated level of involvement in a given positive core. When the Epstein criteria were developed, the standard technique in use at The Johns Hopkins Hospital was a sextant (i.e., six-core) biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the probability of detecting prostate carcinoma and the accuracy of pathologic grading both increase with increasing number of biopsy cores obtained. 12,13 The number of cores found to be positive for malignancy also varies according to the number of cores obtained, as does the probability of detecting an elevated level of involvement in a given positive core. When the Epstein criteria were developed, the standard technique in use at The Johns Hopkins Hospital was a sextant (i.e., six-core) biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][12][13][14] Technical aspects of needle biopsy that may have an impact on Gleason grading, including the use of ultrasound for guidance, the size of needle used, and the number of cores obtained, all have changed over time. 19 Similarly, the diminishing rates of transurethral resection may contribute to changes in the spectrum of prostate cancers that are diagnosed. 20 Nonetheless, clear trends can be discerned from previous studies regarding the distribution of GS on RRP specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The major unmet need is the lack of definitive prostate imaging that can discriminate likely carcinoma from focal inflammation, atrophy, scarring, etc. Because the biopsies are not directed at suspicious lesions, arguments continue to rage over the pattern of sampling, the zonal regions of the prostate to be sampled, the number of core samples to be taken, and when or whether repeat biopsy procedures should be pursued if prostate cancer is not detected (62,63). Of interest, serum testing for bound vs. free serum PSA was approved as a tool for reducing unnecessary prostate biopsies in men with an elevated serum PSA (64).…”
mentioning
confidence: 98%